Improving Physical Endurance in Palliative Stage IV Lung Cancer: A Case Report - Hidayati, Evi Rachmawati Nur; Akhir, Choirunnisa Yaumal; Zatirah, Irvi Addini (Indonesian Society of Respirology (ISR), 2025)
Background: Lung cancer remains the leading cause of cancer-related mortality worldwide, with advanced stages often causing fatigue, reduced endurance, and impaired lung function. Pulmonary rehabilitation, including incentive spirometry exercise (ISE) and aerobic exercise, has been proven effective in improving functional capacity in patients with lung cancer, even in palliative care settings. This case report examines the effects of ISE and aerobic exercise on a stage IV lung cancer patient. Case: A 58-year-old male with stage IV lung cancer and spinal metastases experienced increased fatigue, especially after walking 500 meters. He underwent a four-weeks palliative rehabilitation program that included individualized supportive exercises (ISE) and moderate aerobic activity. Discussion: Following the completion of the program, the patient showed improvements in respiratory function, thoracic expansion, walking ability and overall performance status. His walking distance increased from 450 meters to 522 meters, and his MET score improved, indicating an enhancement in cardiovascular fitness. Despite a decline in forced vital capacity (FVC), other indicators show significant improvements in his physical function and quality of life. Conclusion: The combination of ISE and aerobic exercise proves to be an effective rehabilitation approach in improving respiratory function, physical endurance, and quality of life with stage IV lung cancer, even within the palliative care phase.